(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2019)
The anthropic changes in vegetation occur under the influence of powerful external factors associated with human activity. In the valley of the Kuyalnitskyi estuary, the anthropic changes exceed natural in terms of its scale and degree of influence. The main factors of such changes are pasture, pyrogenic, phenicial, recreational and a number of man-made. The halophytic and halophytic meadow vegetation of the coastal areas of the lower reaches of the Velykyi Kuyalnik and the estuary are most affected by the pasture. The steppe and shrub vegetation of the slopes of the valley are influenced a pyrogenic factor and forest logging. The influence of the phenicial and recreational factors are manifested on a narrower scale. The action of local anthropic factors are enhanced by the action of global or local natural factors. The complex effect of local grazing and global climatic factors on halophytic-meadow and steppe communities are lead to their unification, loss of the autochthonous elements and formation unproductive associations Aegilopsetum cylindricae Buia et al. 1969, Hordeetum murini Libbert 1932, Anisantho-Artemisietum austriacae Kostylev 1985 on the coast. Modern steppe vegetation of the valley slopes was formed under the influence of a pyrogenic factor. It intensifies desertification processes, which occur under the influence of geomorphogenic and climatic factors. Subsequently, frequent fires will result in substitution of desert-steppe zone steppe groups with domination of Agropyron pectinatum, Elytrigia repens, E. intermedia and Ephedra distachia. Forest melioration was carried out by means of terracing the slopes. These violates the processes of historical development of the steppe and significantly changes the environment, which violates the natural development of flora and vegetation. Elaeagnus angustifolia, E. commutata and Cotinus coggygria have a strong expansive activity. The first two species formed a strip of woody vegetation around the estuary, displacing the natural halophyte-meadow groups. The last species forms very dense thickets on many parts of the right-bank slopes. The regeneration of indigenous steppe vegetation occurs quite slowly in areas were tree-shrub plantations perished.